LGG-46. Survival Of The Fittest? A Prognostic Evaluation of Paediatric Low-Grade Glioma (PLGG) Survivor Functional Outcomes. (3rd June 2022) - Green, Katherine; Dahl, Christine; Jorgensen, Mette; O'Hare, Patricia; Opocher, Enrico; Slater, Olga; Gains, Jenny; Chang, Yen-Ching; Aquilina, Kristian; Bowman, Richard; Oldridge, Bronwen; Jacques, Thomas S; et al.
Abstract: INTRODUCTION : Whilst most patients with PLGG will survive, varying morbidities derived from patient, tumour & treatment characteristics can afflict life-long disabling functional impairments. No PLGG studies have evaluated potential prognostic factors for important functional outcomes. METHODS : We performed retrospective analysis of all children diagnosed with PLGG at GOSH 1980-2021.Review of medical notes recorded patient demographics, tumour characteristics & treatment data.Functional outcomes included endocrine, educational, visual (in OPG), auditory & physical function.Multivariate regression analysis(p<0.05) examined associations between biological prognostic variables & functional outcomes. RESULTS : 814 patients were diagnosed with PLGG.731(90%) had 5-years follow-up from diagnosis & were included for functional analysis.Median age at diagnosis 7 years(0-17.9); 50.6%Male, 12.2% NF1.Tumours were cerebral(27%), cerebellar(27%), hypothalamo-chiasmatic(19%), brainstem(7%), or other(20%);with disseminated disease in 5%.Pilocytic Astrocytoma constituted 46%.Molecular profiling of 133 revealed 5% BRAFV600E mutation, 42% BRAF-KIAA1549 fusion.Treatments included: Surgery(70%), Chemotherapy(20%), & Radiotherapy(21%).20-year-OS 94%, PFS 76%;median follow-up 16 years(5-38). Documented neurocognitive deficiency(30%) associated with chemotherapy(HR2.36, 95%CI 1.49-3.75, P<0.001), radiotherapy(HR 2.25, 95%CI1.5-3.36, P<0.001) & male gender(HR 0.68, 95%CI 0.49-0.95, P0.02)as independent poor-prognostic risk-factors.Chemotherapy(HR 5.7, 95%CI1.4-22.3, P0.01) & radiotherapy(HR6.77, 95%CI2.1-22.0, P0.001) were independent risk-factors for requirement of Educational-Health-Care-Plans(25%).9% attended specialised schools. Combined-limb-MRC-grade <18/20(6.4%) was independently-associated with receiving chemotherapy(HR 2.77, 95%CI1.29-5.93, P0.01), & radiotherapy(HR 6.28, 95%CI3.25-12.15, P<0.001).6% mobilised by wheelchair.Resolution of seizures occurred in 68% of 176 following PLGG treatment. Single/multiple endocrinopathies occurred in 9.3%/11%.Presence of 2+Endocrinopathies was associated with chemotherapy(HR6.82, 95%CI4.0-14.4, P<0.001), radiotherapy(HR7.81, 95%CI4.3-14.3, P<0.001), NF1(HR2.9, 95%CI1.3-6, P0.01), OPGs(HR 1.3, 95%CI1.2-1.5, P<0.001);with younger diagnostic-age(HR0.80, 95%CI0.74-0.87, P<0.001) & initial surgical resection(HR0.3, 95%CI0.15-0.7, P0.03) independent protective factors. Receiving chemotherapy/radiotherapy were independent prognostic-factors for Post-PLGG-treatment Brock grade 1+ hearing impairments(2.2%).Visual outcomes in 146 OPG patients:blindness in atleast 1 eye(4.8%), registered visual impairment(9.6%), & visual-aid use(6.2%). CONCLUSIONS : Whilst overall outcomes for PLGG are optimistic, some patients have significant functional impairments detrimental to quality-of-life.Further evaluation of longer-term functional outcomes and prognostic associations is justified.